Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12936-015-0916-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interactions between artesunate-mefloquine and ritonavir-boosted lopinavir in healthy Thai adults

Abstract: BackgroundConcomitant use of anti-malarial and antiretroviral drugs is increasingly frequent in malaria and HIV endemic regions. The aim of the study was to investigate the pharmacokinetic interaction between the anti-malarial drugs, artesunate-mefloquine and the antiretroviral drug, lopinavir boosted with ritonavir (LPV/r).MethodsThe study was an open-label, three-way, sequential, cross-over, pharmacokinetic study in healthy Thai adults. Subjects received the following treatments: Period 1: standard 3-day art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
6
0
1
Order By: Relevance
“…In addition, the existing information is mainly limited to artemisinin derivatives [ 37 , 38 ]. A recent study reported potential pharmacokinetic interactions between MQ-Artesunate (MQ-AS) and lopinavir (LPV/r) in adults, with a reduction in systemic exposure of both drug combinations, suggesting a higher risk of treatment failure for both malaria and HIV infection when the two drugs are co-administered [ 39 ]. Another limitation of our study was that data on adherence and on average duration of ARV drugs administration before delivery, which are known to determine viral suppression, was not available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the existing information is mainly limited to artemisinin derivatives [ 37 , 38 ]. A recent study reported potential pharmacokinetic interactions between MQ-Artesunate (MQ-AS) and lopinavir (LPV/r) in adults, with a reduction in systemic exposure of both drug combinations, suggesting a higher risk of treatment failure for both malaria and HIV infection when the two drugs are co-administered [ 39 ]. Another limitation of our study was that data on adherence and on average duration of ARV drugs administration before delivery, which are known to determine viral suppression, was not available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analysis showed that mutation of the Kelch-13 propeller did not affect the pharmacokinetic parameters of mefloquine. The significant influence of artesunate administration on mefloquine pharmacokinetics is unlikely [ 45 , 46 ] and was not included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the above potential interactions have been confirmed in pharmacokinetic studies involving ARV drugs and ACTs. [73][74][75][76] Clinical studies are required to determine the impact of these interactions on parasitaemia, efficacy and toxicity of antimalarial therapy in adult population of HIV-infected patients with malaria co-morbidity.…”
Section: Potential Csdis Between Arvs and Antimicrobial Drugsmentioning
confidence: 99%